2016
DOI: 10.1182/blood.v128.22.145.145
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab Maintenance after Autologous Stem Cell Transplantation Prolongs Survival in Younger Patients with Mantle Cell Lymphoma: Final Results of the Randomized Phase 3 LyMa Trial of the Lysa/Goelams Group

Abstract: Mantle cell lymphoma (MCL) accounts for approximately 6% of non-Hodgkin's Lymphoma (NHL) in adults. MCL commonly responds to initial therapy but inevitably patients relapse and response duration decreases from one salvage therapy to the next. Indeed, there is an urgent need to control and/or eradicate residual MCL cells that are responsible for early and late relapses. Maintenance with Rituximab (RM) after R-CHOP has been shown to prolong OS in elderly MCL patients treated with R-CHOP (Kluin-Nelemans et al. NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…The role of ASCT in CR1 has not been tested in a randomized trial. However in a retrospective analysis of 167 MCL patients under age 65, the patients received either R‐HyperCVAD or R‐CHOP followed by an auto ASCT in CR1 had an improved PFS compared to R‐CHOP alone ( P < .004), even when corrected for prognostic factors . The best induction regimen before transplant has not been defined, but the ability to attain a CR may be the most important characteristic.…”
Section: Risk‐adapted Therapymentioning
confidence: 93%
“…The role of ASCT in CR1 has not been tested in a randomized trial. However in a retrospective analysis of 167 MCL patients under age 65, the patients received either R‐HyperCVAD or R‐CHOP followed by an auto ASCT in CR1 had an improved PFS compared to R‐CHOP alone ( P < .004), even when corrected for prognostic factors . The best induction regimen before transplant has not been defined, but the ability to attain a CR may be the most important characteristic.…”
Section: Risk‐adapted Therapymentioning
confidence: 93%
“…Indeed, several studies have shown rituximab to be effective in re‐inducing molecular remission after ASCT in 80–100% of cases (Brugger et al , ; Ladetto et al , ; Andersen et al , ; Kolstad et al , ). Furthermore, a recently presented randomized trial showed that rituximab maintenance after ASCT improved PFS and OS (Le Gouill et al , ). Because rituximab is costly and associated with possible adverse effects, such as cytopenias, infection and hypogammaglobulinaemia, the ability to target at‐risk patients would be worthwhile, and may be provided by MRD measurements.…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%
“…With a median follow-up of 50.2 months, patients randomized to the MR arm demonstrated a significantly improved 4-year EFS (78.9% vs 61.4%; P = 0.001) and 4-year OS (88.7% vs 81.4%; P = 0.041) compared with observation. 33 In a large randomized trial, the CALGB 50403 study investigated the efficacy of bortezomib therapy post ASCT. Patients were treated with an R-CHOP based induction regimen along with methotrexate, followed by chemomobilization with etoposide, cytarabine and rituximab before receiving high-dose chemotherapy and ASCT.…”
Section: Mantle Cell Lymphomamentioning
confidence: 99%